Analysing the Negative Impact of Game-Based Online Quizzes toward Students’ Learning Motivation in Digital Era - RAHMAN, PATUR (Universitas Islam Negeri Alauddin Makassar, 2025)
Nowadays, education is undergoing a significant transformation, particularly in teaching methods that increasingly integrate technology. The use of technology-based teaching media, such as game-based online quizzes, has become a trend, especially among university students. Although game-based online quizzes like Quizizz demonstrate significant benefits in enhancing learning motivation, evaluating students, and making learning more engaging, there are negative impacts in their application. This study aims to delve deeper into the psychological impacts of using Quizizz on students' learning motivation, focusing on exploring students' general experiences and the negative effects of using the game-based platform. Qualitatively, the study employed a phenomenological approach using semi-structured interviews with 20 respondents selected from four different study programs across three academic years (2021, 2022, 2023). The findings revealed a dominant impression among students that Quizizz is an enjoyable evaluation platform for learning, effectively strengthen teaching material, serves as a flexible learning medium, and provides immediate feedback during evaluations. However, on the other side, Quizizz fosters premature satisfaction among students, leads to inefficient teaching time due to internet connectivity issues, encourages guessing answers rather than understanding questions, decreases narrative and written communication skills if overused in evaluations, opens opportunities for digital cheating, and potentially demotivates students due to psychological factors such as feelings of embarrassment from publicized failures. This could result in self-labelling with internalized failure.